The Willingness of Undergraduate Nursing Students Regarding Utilizing CAM as a Preventative Method of Coronaviruses - Barnawi, Najla A.; Al-Ghadeer, Hind S.; BinSaran, Madhawi M.; Bin-Muneef, Walaa, S.; Alroilai, Maryam S.; Alahmed, Shahad M. (International Journal of Innovative Research in Medical Science, 2021)
In response to the global awareness about the Coronavirus, mainly COVID-19, developing an educational-video tool regarding the utilization of Complementary and Alternative Medicine (CAM) as a preventative method of Coronaviruses. It is an ideal resource for nursing students, who are a cornerstone of the continuity of care and partnerships with high-risk individuals, families, and communities. This study examines the impact of the CAM video session on the level of attitude among Saudi undergraduate female nursing students in Riyadh, Saudi Arabia. A pre-post tests quasi-experimental study was conducted among 174 students to examine their attitude changes before and after they exposed the CAM educational video. The results suggesting that the CAM video session significantly improves students’ attitudes (M(differences) = 55.2068, SD = 5.9964, [t(174) = 121.444, p < .001]); Further, the number of utilizing the CAM therapy mainly the herbal methods was increased after the exposure to CAM video (pre-test n= 76, 43.7% vs. post-test n= 130, 74.7%). In conclusion enhancing the students' attitudes toward utilizing CAM therapy as preventive measures is a core aspect of public health. Further, implementing such attractive, simple, and evidence-based tools increases the utilization of accessible and available CAM resources such as herbal remedies. Accordingly, there is a need to examine the CAM video tool at a larger scale and not merely focus on the healthcare professionals but should include population-based scope.